Dakwah among Aborigines: Orang Asli at Gua Musang - Noor Haslinda Bt Mat Ripin (Kolej Universiti Islam Malaysia, 2011)
An aborigine is original people who are lived in one state. Based on the research, most of the aborigines are so difficult to accept Islam as their religion because they think if they convert to Islam means that they must follow all Islamic regulation. On their capture, Islam is difficult religion to accomplish because it is so many regulations that will follow by them. As a result, they must leave their daily practice. They also think that they will be Malaysian if they convert to Islam. Therefore, to get true knowledge about this problem, research was done at Pos Pasik, Pos Simpor, Pos Blau, Pos Kuala Wok and Kg. Redid.